Taken for a ride : fraud at the Ministry of Transport - Gee, Debbie, (SAGE Knowledge. Cases., 2019)
This case covers a high-profile public sector criminal case of prolonged and serious fraud by a former senior manager, Joanne Harrison, at New Zealand's Ministry of Transport that went unchecked for five years, despite attempts by employees to draw attention to her repeated non-compliance with procurement policies. An independent inquiry later confirmed allegations by four staff who raised concerns that they were subsequently disadvantaged in various ways in their employment at the ministry. Martin Matthews, chief executive of the ministry at the time of Harrison's offending, was subsequently appointed New Zealand's Auditor-General, responsible for auditing all public entities in the country. Matthews asked for a parliamentary inquiry into allegations about his handling of these issues but resigned before it was concluded. This case raises questions about the adequacy of whistleblowing legislation and policies and the importance of organisational culture and leadership in creating and maintaining a cultural environment that supports ethical behaviour and protects staff who try to flag what they believe is inappropriate behaviour.